Efecto de la aplicación foliar y drench de humus líquido y algas marinas, en el cultivo de maíz duro (Zea mays L) - Punina Yauqui, Edwin Leonardo (2023)
Corn is one of the most important cereals in the world, production for 2016 was 1060 million tons, in the United States, China, Brazil, the European Union, Argentina, and Mexico. For 2020, the harvested area of corn in Ecuador was 355,913 hectares, with a production of 1,358,626 tons. The province of Los Ríos reached 47% of the national production. The objectives of this research were: Identify the method of foliar or drench application and the frequency that provided greater productivity; Determine the dose that contributed to a higher production of the corn crop; Establish the benefit/cost ratio (B/C) in each of the treatments. This research was carried out in the province of Los Ríos, Vinces canton, Lechugal site, using an experimental design of Randomized Complete Blocks (DBCA) in a factorial arrangement of 4 x 3 x 3 repetitions. Factor A: Methods and frequencies of application and Factor B: Dosage of earthworm humus and marine algae. Based on the analysis and interpretation of the results obtained in this investigation, it is concluded: In Factor A, the best yield was A2 with 6317.7 kilograms of corn per hertare in this agroecological zone. Factor B1 registered the best yield per hectare with 6069.4 kilograms. In the A x B interaction, the treatment with the highest yield was T4 with 7209.9 kg/ha. Economically, the technological alternative with a net benefit of $5.53 USD was T4 with a benefit/cost ratio: B/C of $1.37 USD and an income/cost ratio I/C of $0.37 USD.